Investigating acute effects of oncolytic virus infection of tumours - Breitbach, Caroline (University of Ottawa (Canada), 2009)
Oncolytic viruses (OVs) are selected or designed to eliminate malignancies by direct infection and lysis of cancer cells. In contrast to this concept of direct tumour lysis by viral infection, a significant portion of the in vivo tumour killing activity of two OVs, vesicular stomatitis virus (VSV) and vaccinia virus is caused by indirect killing of uninfected tumour cells. Limited virus infection rapidly triggers a loss of tumour perfusion within the tumour core. Tumour cells within the tumour rim remain viable and are associated with intact vasculature. Transcript profiling of tumours demonstrates a pro-inflammatory gene signature with significant induction of neutrophil chemo-attractants. Depletion of neutrophils in animals prior to VSV administration eliminates uninfected tumour cell apoptosis and permits more extensive replication and spreading of the virus throughout the tumour. Tumour targeted inflammation triggers extensive intravascular coagulation which is responsible for the loss of perfusion as inhibition of coagulation results in maintenance of tumour perfusion in the context of VSV therapy. Interestingly, the remaining viable tumour rim does not expand in tumours implanted into immune competent mice. Conversely, a massive expansion of the viable tumour rim ensues following treatment of tumour bearing nude mice that possess a defective adaptive T cell response. These results suggest that outgrowth of viable tumour cells from the tumour rim following OV therapy is inhibited by an adaptive immune response triggered to target tumour cells. Taken all together, these results indicate that targeted recruitment of neutrophils triggers coagulation within infected tumour beds and enhances the killing of malignant cells. Activation of inflammatory cells may be used for enhancing the effectiveness of oncolytic virus therapeutics as well as other anticancer agents that may similarly trigger inflammation. Understanding mechanism and consequences of inflammation dependent tumour cell death is important as loss of tumour perfusion has now also been measured in patients treated with vaccinia virus.
Keywords: Chemistry, Biochemistry.; Health Sciences, Oncology.